PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI SUB SEKTOR OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Marismiati Marismiati; Pestauli Agatha (LAND JOURNAL, 2026)
The sector which has an important contribution to the country’s economic growth is the automotive industry. In its operations, large companies naturally employ a financial dramework that includes the utilization of debt and the generation or earnings as the basis of performance, which can influence the stock value received by investors. High levels of debt may increase financial risk, while good profitability attracts investors to invest their capital. This research is centered to examine the relationship between leverage and profitability on stock prices in automotive sub-sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. The researcher applied a quantitative method with an associative approach. Through purposive sampling, 10 companies were selected as the research objects. The data source was obtained from annual financial statements published on the official website of the Indonesia Stock Exchange. The data analysis techniques used include Descriptive Statistics, Classical Assumption Tests, Multiple Correlation Analysis, Multiple Regression Analysis, Coefficient of Determination, t-test, and F-test. This study is expected to provide clear evidence regarding the effect of leverage and profitability on stock prices and serve as a consideration for investors, companies, and academics.